CT45A1‐mediated MLC2 (MYL9) phosphorylation promotes natural killer cell resistance and outer cell fate in a cell‐in‐cell structure, potentiating the progression of microsatellite instability‐high colorectal cancer - Hao‐Wei Teng; Hsiang‐Yueh Huang; Chun‐Chi Lin; Yuh‐Ching Twu; Wen‐Hao Yang; Wen‐Chun Lin; Hsin‐Yi Lan; Yen‐Yu Lin; Wei‐Lun Hwang (Molecular Oncology)
Patients with microsatellite instability‐high (MSI‐H) colorectal cancer (CRC) have high tumor mutation burden and tumor immunogenicity, exhibiting a higher response rate to immunotherapy and better survival. However, a portion of MSI‐H CRC patients still experience adverse disease outcomes. We aimed to identify the tumor‐autonomous regulators determining these heterogeneous clinical outcomes. The Cancer Genome Atlas (TCGA) dataset was used to identify regulators in MSI‐H CRC patients with unfavorable outcomes. Stable CRC tumor clones expressing targeted regulators were established to evaluate migratory and stemness properties, immune cell vulnerability, and cell‐in‐cell (CIC) structure formation. RNA‐sequencing (RNA‐seq) was used to identify enriched biological pathways in stable CRC tumor clones. Clinicopathological characterization of formalin‐fixed paraffin‐embedded (FFPE) MSI‐H CRC specimens was performed to explore the underlying mechanisms involved. We showed that cancer/testis antigen family 45 member A1 (CT45A1) expression was upregulated in MSI‐H CRC patients with poor survival outcomes. CT45A1‐expressing microsatellite stable (MSS) CRC cells showed enhanced migratory ability. However, CT45A1‐expressing MSI‐H CRC cells, but not MSS CRC cells, showed higher resistance to natural killer (NK) cell cytotoxicity and served as outer cells in homotypic CIC structures, preventing exogenous or therapeutic antibody access to inner CRC cells. Inactivating RHO‐ROCK/MLCK‐MLC2 signaling with small‐molecule inhibitors or short‐hairpin RNAs (shRNAs) targeting myosin light chain kinase (MYLK) abolished NK cell resistance and reduced the outer cell fate of CT45A1‐expressing MSI‐H CRC cells. In MSI‐H CRC patients, CT45A1‐positive tumors exhibited increased MLC2 phosphorylation, increased outer cell fate, and decreased survival. We demonstrated that CT45A1 potentiates the advanced progression of MSI‐H CRC, and targeting MLC2 phosphorylation may enhance immunotherapy efficacy in CT45A1‐positive MSI‐H CRC patients.